Students’ View about Attitude and Aptitude Test of Students in the Selection Process of MBBS Course in Bangladesh (Bangladesh Journal of Medical Education, 2022)
Attitude and aptitude are the two important criteria to select medical professionals. Interest for the subject is a pre requisite as well as students need high levels of motivation, intelligence and stamina to cope up with the stresses encountering in the steps of medical profession. Currently, no research is found to identify attitude and aptitude of students as selection criteria of MBBS course of Bangladesh. This descriptive type of cross sectional study was carried out from January 2021 to December 2021, among 617 undergraduate medical students of 8 medical colleges of Bangladesh. Data were collected by self-administered pre tested structured questionnaire, then compiled and analysed using SPSS version 26. Regarding need of attitude test, the study revealed that 97.7% students and regarding aptitude test 90.8% students were agreed. Among the reasons in favour of attitude test, maximum (54.89%) students were agreed about the statement “Cause of their eagerness to enrol into this course will be known”. Regarding reasons in favour of aptitude test, mean score were above 4 (out of 5) by majority (90.8%) of students in selected 4 areas of professionalism-1) Knowledge, skill and performance, 2) Safety and quality of treatment, 3) Communication and teamwork and 4) Morality and gaining trust. The study emphasizes that attitude and aptitude test are essential need for the MBBS candidates. So, the tests may be the essential part selection process.Bangladesh Journal of Medical Education Vol.13(2) July 2022: 3-12